Identification of Mycobacterium marinum in subcutaneous abscesses of an infected patient's foot - Wei, Yong; Zhang, Jiachun; Xin, Xuli; Wu, Yang; Wang, Lin; Guo, Kai; Xu, Yingchun; He, Song (The Journal of Infection in Developing Countries, 2024)
Introduction: Mycobacterium marinum is a well-known pathogenic non-tuberculous mycobacterium for skin and soft tissue infections. Infection, often presenting as superficial lesions, is seen after exposure of skin abrasions to contaminated water or infected fish and is known as “swimming pool” or “fish tank” granuloma. This study reported a case of M. marinum infection in subcutaneous abscesses of a patients' foot. Methodology: A diagnosis of M. marinum infection was established with the help of tissue biopsy, culture, matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) and molecular analysis. Results: The patient was diagnosed with M. marinum infection in his left foot and received appropriate antibiotic treatment with the desired effect. Conclusions: In many parts of the developing world, M. marinum infections may remain undiagnosed due to limited symptoms, as well as the lack of medical services and laboratory facilities. Key diagnostic elements for M. marinum infections include a high index of suspicion raised by chronic lesions, poor response to conventional treatments, a properly obtained exposure history, culture, and microorganism identification. This study provides some references and suggestions for the clinical characteristics, diagnosis, treatment and prevention of M. marinum infection.